How to feel good : 20 things teens can do - Mangan, Tricia (Washington, DC : Magination Press, 2012)
Provides twenty mind-healthy skills for teenagers, with tips on self-awareness, and how to teach yourself to stay calm and self-confident.
Have a positive attitude -- Shine a spotlight on good things -- Compare to no one, you're an original -- Discover what you can do -- Make friends with your feelings -- Live in the present -- Chase your fears -- Cut your problems into pieces -- Conquer problematic procrastination -- Expand your world -- Speak for yourself -- Forgive to feel better -- Be kind to your whole self -- Practice being patient -- Control what you can -- Switch shoes -- Spring back -- Choose where you want to go -- Comfort yourself -- Appreciate your own hard work.
Young Adult.
Young Adult
Keywords: Adolescent psychology; Teenagers -- Life skills guides; Teenagers -- Conduct of life; Adolescent psychology; Teenagers -- Life skills guides; Teenagers -- Conduct of life